Analisis Kesiapan Penerapan Rekam Medis Elektronik di Klinik Mata Madiun - Eltigeka Devi Apriliani; Al Wafi Rahmaputri Ardianingrum; Tiara Putri Maharani (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Healthcare facilities in Indonesia are required to implementation of electronic medical records. The implementation of electronic medical record still obstacles and has not evenly. The aims of this research to analyze the readiness of the implementation of electronic medical record in Klinik Mata Madiun. This study uses a quantitative descriptive method with the instrument of Doctor’s Office Quality Information Technology (DOQ-IT). The population in this study were all user officers of electronic medical record, with a sample size of 19 respondents selected using the total sampling technique. The result of human resources aspect obtained a score of 2.8, which falls into the moderately ready category. The organizational work culture aspect obtained a score of 3.5, which falls into the highly prepared category. The leadership governance aspect obtained a score of 3.1, which falls into the moderately ready category. The IT infrastructure aspect obtained a score of 2.6, which also falls into the moderately ready category. The total overall score for the readiness of Electronic Medical Record (EMR) implementation at Klinik Mata Madiun is 86.5, into Category II and indicates that Klinik Mata Madiun is Moderately Ready to implementation the Electronic Medical Record. The result of study that several components have demonstrates strong and weak capabilities. The components have demonstrates strong and weak capabilities. Further identification and anticipation of weak components are needed to ensure optimal implementation of electronic medical record in the Klinik Mata Madiun.